Developing Management Information System for Problem-Check-List (DCM) Instrumentation Management to Support Counseling Guidance Teacher Work Program at SMA Negeri 1 Ambarawa, Semarang Regency - Kustiyono, Kustiyono (Cattleya Darmaya Fortuna, 2023)
The advancement of information systems is pervasive across numerous sectors, including industry and academic institutions. Similarly, the establishment of an information system at SMA Negeri 1 Ambarawa, Semarang Regency for the purpose of ascertaining the work schedules of counseling guidance teachers, remains traditional in nature. The conventional system continues to have a number of flaws, including the following: Obtaining data from students regarding issues that arise is time-consuming, possibly spanning several days or weeks, due to the need to distribute completed questionnaires to each class. Additionally, the counseling guidance teacher must carry out the calculation process alone. Each piece of data acquired from the student is subsequently computed based on their capability to perform the calculation procedure. Devoting a substantial amount of time and effort to this endeavor renders it ineffective. Counseling guidance teachers require a significant amount of time to develop a problem-check list learning implementation plan due to the fact that they must individually create a problem-check list (Daftar Cek Maasalah or DCM) for each student. A Management Information System for DCM Instrumentation Management is required to assist Counseling Guidance Teacher Work Program in light of these deficiencies. The preparation of work programs, which are learning implementation plans that incorporate DCM instrumentation applications that must be integrated into a computerized information system to improve school performance, are expected to be facilitated by this information system.